Structure and stability in the community with the endangered plant Heritiera parvifolia Merr. (Malvaceae) in lowland rainforest in Diaoluo mountain of Hainan Island, China - Shang, Naiyan; He, Shaocui; Qi, Dongling; Yang, Xiaobo; Li, Donghai; Liu, Rentong; Du, Chunyan; Su, Xin; Qi, Tianyun (Frontiers in Plant Science, 2025)
IntroductionEndangered plants are crucial for ecosystem stability, influencing forest community structure. However, commercial logging and the expansion of economic forests have led to tropical forest habitat degradation and fragmentation.MethodsTo assess the community structure and stability of Heritiera parvifolia, an endangered plant, in the Diaoluo Mountain zone of National Park of Hainan Tropical Rainforest in China, a field study was conducted across 20 plots. The analysis utilized species diversity indices, principal component analysis, ward clustering, linear regression, and one-factor analysis of variance.ResultsThe results showed high species richness in the community, with 78 families, 196 genera, and 302 species. Dominant families include Rubiaceae, Euphorbiaceae, and Lauraceae. The species richness, Shannon index, and Simpson index for the arbor and shrub layers were significantly higher than those of the herbaceous layer (P < 0.001), while the Pielou index was also higher (P < 0.01). Cluster analysis indicated that plots with less human disturbance (Group I) had greater stability than those with more disturbance (Group II). The stability index positively correlated with stand density, proportion of mature trees, average diameter at breast height and average tree height of dominant trees (P < 0.05), all of which were key factors in community stability. Stability was also significantly influenced by altitude and slope aspect, with significant differences observed between altitudes of 200–299 m and 400–499 m (P < 0.05), and between southeast slopes and other aspects (P < 0.05).DiscussionThis study highlights the factors affecting the stability of H. parvifolia communities, providing insights for conservation, biodiversity protection, and rainforest restoration.